Literature Review: Risk Factors For Hypertension In Pregnancy - Yushi Mindarani; Fadli Ananda; Andi Emilda; Mona Nulanda; Nuraini Abidin (Sean Institute, 2024)
Hypertension in pregnancy is an important cause of severe acute morbidity, long-term disability and maternal and infant mortality. Hypertension in Pregnancy (HDK) is defined as blood pressure ≥140/90 mmHg in two or more measurements with onset more than 20 weeks of gestation, and no previous history of hypertension. In Indonesia, hypertension in pregnancy is the second highest cause of maternal death after bleeding. (4) The prevalence of hypertension in pregnancy in Indonesia was recorded as being found in 8341 cases (1.51%) of pregnant women from all samples of women aged 15–54 years. There are many risk factors that can cause an increase in blood pressure during pregnancy, such as primigravida, multiple pregnancies, hydatidiform mole, diabetes mellitus, hydrops fetalis, macrosomia, age less than 20 years or more than 35 years, family history of hypertension. pregnancy, previous history of hypertension, kidney disease, and obesity.